Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Review - Page 476: 83



Work Step by Step

2$x^{2}$+2x-24=2($x^{2}$+x-12)= 2($x^{2}$+4x-3x-12)=2[x(x+4)-3(x+4)]= 2(x-3)(x+4)
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.